Thy-1+/− fibroblast subsets in the human peritoneum - Kawka, Edyta; Bartosova, Maria; Schäfer, Betti; Schmitt, Claus P. (American journal of physiology. Renal physiology, 2017)
Fibrotic thickening of the peritoneum develops in patients receiving peritoneal dialysis (PD) for renal failure. For unknown reasons, however, in some patients it progresses to extensive fibrosis that compromises dialysis capacity of the peritoneum. It is increasingly clear that fibroblasts display large heterogeneity not only between but also within tissues. Differential surface expression of thymocyte differentiation antigen 1 (Thy-1) has been shown to identify functionally distinct fibroblast subsets in several organs. Here, we isolated Thy-1+/− subsets of human peritoneal fibroblasts (HPFB) and analyzed them in terms of profibrotic myofibroblast features. In healthy individuals, Thy-1+ cells constituted ~45% of the HPFB population found in the greater omentum but were not detected in the parietal peritoneum. When propagated in culture and compared with Thy-1− cells, omentum-derived Thy-1+ HPFB consistently displayed an increased expression of α-smooth muscle actin, collagen I, and transforming growth factor-β1. They also showed greater proliferation capacity and enhanced contractile properties. The number of Thy-1+ HPFB increased significantly in PD patients and made up more than 70 and 95% of all HPFB found in the omentum and parietal peritoneum, respectively. These data indicate that the expansion of Thy-1+ fibroblasts may contribute to fibrotic thickening of the peritoneal membrane during PD.
Gesehen am 30.07.2018